2011
DOI: 10.1186/1471-2334-11-86
|View full text |Cite
|
Sign up to set email alerts
|

Female gender predicts lower access and adherence to antiretroviral therapy in a setting of free healthcare

Abstract: BackgroundBarriers to HIV treatment among injection drug users (IDU) are a major public health concern. However, there remain few long-term studies investigating key demographic and behavioral factors - and gender differences in particular - that may pose barriers to antiretroviral therapy (ART), especially in settings with universal healthcare. We evaluated access and adherence to ART in a long-term cohort of HIV-positive IDU in a setting where medical care and antiretroviral therapy are provided free of char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
80
3
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 26 publications
4
80
3
3
Order By: Relevance
“…In contrast, a study among Canadian cohort of HIV-positive, authors reported that female gender was independently associated with a lower likelihood of being adherent to ART (OR = 0.70; 95% Cl: 0.53-0.93), after adjusting for clinical characteristics as well as drug use patterns measured longitudinally throughout follow-up [17].…”
Section: Factors Associated With Adherence To Artmentioning
confidence: 84%
“…In contrast, a study among Canadian cohort of HIV-positive, authors reported that female gender was independently associated with a lower likelihood of being adherent to ART (OR = 0.70; 95% Cl: 0.53-0.93), after adjusting for clinical characteristics as well as drug use patterns measured longitudinally throughout follow-up [17].…”
Section: Factors Associated With Adherence To Artmentioning
confidence: 84%
“…Previous Canadian studies have shown that women experience poorer HIV-related clinical outcomes compared with men, mediated by suboptimal engagement and retention within HIV services and lower adherence to antiretroviral therapy. [18][19][20][21]25,26 Inconsistent condom use among women living with HIV is well-described in the literature, attributed to fertility desire and serocondordant partnerships, in addition to challenges negotiating condom use, including gendered power imbalances, fear of inadvertent status disclosure and the threat of violence. [27][28][29][30] Marginalized women living with HIV may experience additional social-structural barriers to insisting upon safer sex practices, particularly those who are economically disadvantaged and who engage in survival sex work, 8,31,32 compromising their ability to avoid criminal liability for HIV nondisclosure through both achievement of a low viral load and condom use.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of the authors' knowledge there is no study comparing fusion rates of 1st MTPJ arthrodesis in male and female patients. However, treatment adherence comparisons by gender have been made in other medical specialties and demonstrate conflicting results [27,28]. It is understood that a successful arthrodesis is a balance between fusion of the joint and implant failure.…”
Section: Discussionmentioning
confidence: 96%